Motivating at work (Menlo Park, Calif. : Crisp Learning, 2001)
This cd-rom program will helps user to raise expectations and perfomance, learn how to create a motivating workplace and increase productivity with the learn method
This self-directed learning package includes Window compatible CD and fifty-minute series workbook
Workbook title : Motivating at work : empowering employees to give their best
System requirements : Windows 85 or later or Windows NT4 or later; pentium (90MHz or fster); Hard disk with 3 MB free;16 MB memory (RAM), 2x faster CD-ROM drive; high colour monitor resolution
Keywords: Motivation (Psychology); Self-actualization (Psychology)